👤


[tex]( \frac{3}{ \sqrt{3} } + \frac{6}{ \sqrt{12} } - \frac{60}{ \sqrt{48} } ) \times \frac{30}{2 \sqrt{75} } [/tex]


Răspuns :

Explicație pas cu pas:

( 3 / √3 + 6 / √12 - 60 / √48 ) × 30 / 2√75 =

= ( 3 / √3 + 6 / 2√3 - 60 / 4√3 ) × 30 / 2 · 5√3

= ( 3 / √3 + 6 / 2√3 - 60 / 4√3 ) × 30 / 10√3

= ( 3√3 / 3 + 6√3 / 6 - 60√3 / 12 ) × 30√3 / 30

= ( √3 + √3 - 5√3 ) × √3

= ( 2√3 - 5√3 ) × √3

= - 3√3 × √3

= - 3 × 3

= - 9

12 I 2

6 I 2  ⇒ 2√3

3 I 3

1

48 I 2

24 I 2

12 I 2  ⇒ 4√3

6 I 2

3 I 3

1

75 I 5

15 I 5   ⇒ 5√3

3 I 3

1